Enhancing academic administrators’ professionalism through the application of development centre - Abdul Rahman, Shukran (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
Given that high quality services of administrations are essential, there must be an effective and continuous development of faculty members who assume leadership roles in higher learning institutions. The efforts to equip them with necessary qualities that determine the effective role as academic administrators and competent managers for higher education and research activities are important in the process of making higher learning institutions excellent centres to boost nation building. True to the emphasis made by the Malaysian Government in developing knowledge workers, worker competencies, and knowledge productivity (Government of Malaysia, 2002), a proper mechanism needs to be strategised in order to bring about desirable characteristics of academic administrators in higher learning institutions